Hubungan Psikologi Pendidikan dengan Belajar di Sekolah Dasar - Muzfirah, Suci; Fitriyani, Anis (Jurnal Pendidikan Educandum, 2023)
Studying educational psychology is the same as studying a branch of science that discusses human behavior in the educational process. In its role, educational psychology makes it easier for teachers to carry out the learning process. The relationship between educational psychology and learning cannot be separated because the two have a reciprocal relationship. The relationship between educational psychology and learning is not just about educational psychology, more than just psychological science in practice, but rather about science or the study of knowledge that has the right to exist independently. This research discusses the nature of psychology, factors that influence children's psychology in the learning process, as well as the relationship between psychology and learning.